Unlocking Gimkit’s Capabilities for Language Classroom - Feldee, Mark; Faresi, Ignatius ((JELE) Journal Of English Language and Education, 2022)
The game has been surely advancing various parts of human cognitive development, one of which is in the field of education. The game can be an effective solution for applying educational content, especially in this pandemic era. It’s believed that through gamifying the classroom, educators can provide a creative-learning environment that enhances engagement, teamwork, and leadership. Gimkit is a game application that was created by a high school student in America. It is one of the results of the kind of environment that support the students to be creative. With so many interesting game modes including human vs. zombie, hidden mode, draw that, until the usual classic multiple-choice, Gimkit shows promising potential in classrooms. This article is based on the exploration on a workshop that we had undergo that shared the many Gimkit modes to be implemented in language classrooms as well as how to build the base question banks. The workshop was divided into three segments which are: Experiencing – playing one of the modes; Creating – building the question banks; and Reflecting – figuring out which part of the learning materials can be gamified using Gimkit. Based on the result, participants got new and creative language teaching ideas using the application Gimkit.